Towards the design of a reflexive regulatory framework to "Reduce and control emissions from land deforestation and degradation and enhancing carbon stocks" (REDD+): a perspective from select developing countries - Munuo, Ngaya Anael (2016)
REDD+ has emerged as one of the governance approaches to address climate change. It calls for developing countries to take part in a second commitment period for a post-2020 climate change regime under the auspices of the United Nations Framework Convention on Climate Change (UNFCCC) and outside the UNFCCC. The goal of REDD+ is that host countries will receive, inter alia, financial compensation if they choose to conserve their forests rather than convert them to non-forest land use. Such compensation is for significant emission reductions which are reasonably attributable to human activities. This implies that REDD+ implementation at a domestic level will require allocation of burdens and benefits. In light of this implication, many scholars suggest that the design of the policy and legal framework to this effect must strike a balance between equity, environmental effectiveness and costeffectiveness (commonly referred to as the 3Es) to be deemed successful. Against this background, this thesis questions: what is the optimal (and feasible) model legislative framework sufficient to implement REDD+? It argues that REDD+ should be defined as a self-regulatory system. This view directs attention toward a distinctive regulatory framework. Thus the thesis suggests that one possible legal framework that holds that potential in Tanzania and Indonesia is reflexive law. The research draws on international best practice and numerous innovative governance models from different fields and proposes essential elements to substantiate its position. This study reflects REDD+ developments up to 31 December 2015